Marine Engines Performance and Emissions II - Lamas Galdo, María Isabel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Marine engines are efficient machines, but stricter legislation about emissions makes continuous research necessary in order to reduce their consumption and improve their efficiency. This Special Issue, "Marine Engines Performance and Emissions II", is a continuation of "Marine Engines Performance and Emissions". It contains a set of peer-reviewed works about marine engine performance and emissions.